Government Support for Open Educational Resources: Policy, Funding, and Strategies - Stacey, Paul (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Foundations like Hewlett, Mellon, and Gates provided start-up funding and support that nurtured the field of open educational resources (OER) from infancy to a robust early adolescence characterized by energy and idealism (Casserly & Smith, 2008). However, foundation grants typically focus on establishing exemplars and cannot be relied on for sustaining ongoing operations or generating widespread adoption. One strategy for sustaining and expanding OER is for governments and public funding to take over from the early stage funding foundations provided (Stacey, 2010).